A Full Immersion Program: The Teachers' and Students' Perceptions and Its Impact on Student's Sense of Nationalism - Hutabarat, Pritz (2014)
The importance of English as a global language is undeniable and to become a competent user of this language is demanded of the time (Oommen, 2012). This study investigates the students' and teachers' perceptions of the implementation of an English full immersion program (FIP) as an alternative approach to teaching English as a foreign/second language within the Indonesian senior high school context. With the growing demands of international-standardized schools, the use of English to deliver non English subjects has become more popular. The purpose of this research is to gain insights from the main parties involved, the students and teachers, to better understand the positive results as well as the potential drawbacks of the program. Ten teachers and fifty nine students from grade ten to twelve participated in the study. Three distinct instruments were used for data collection; a survey questionnaire containing five-point Likert scales; a semi-structured interview; and some field observations. Quantitative data was analyzed by descriptive statistics focusing on the mean of the collected data. The qualitative data of the interviews and field observations were analyzed via content analysis. Results indicate that both the students' and the teachers' have very positive perceptions toward the implementation of an FIP at their school and can really notice the benefits of the program mainly as an effective strategy to develop student's English proficiency level. The concern shared by both parties is mostly related to the attrition in the students' Indonesian language and reduced sense of nationalism. Keywords: Full immersion program (FIP), codification, attrition, Likert scale.